A Hyperlexic-Like Reading Style Is Associated With Increased Autistic Features in Girls With ADHD. Issue 8 (June 2019) - Åsberg Johnels, Jakob; Gillberg, Christopher; Kopp, Svenny
Objective: Hyperlexic-like reading (defined as word decoding much better than comprehension) has been associated with autism spectrum disorder (ASD). Here we study correlates of a hyperlexic-like reading style (HPL) in ADHD, a condition known to co-occur both with reading difficulties and ASD.Method : We compared 10 girls with an ADHD diagnosis plus HPL with 26 with ADHD minus HPL.Results : Girls with HPL scored marginally lower in reading comprehension but did not differ from non-HPL girls in IQ, vocabulary, or in the severity of ADHD ratings. However, in addition to scoring much better on word decoding, HPL readers also displayed higher levels of social-communication deficits on the ADOS-G and the ADI-R. Moreover, correlation analysis in the full sample revealed an association between increasing autistic features and word reading.Conclusion : The study underscores the heterogeneity of reading skills in ADHD, and shows the relevance of subclinic autistic features for understanding this variability.